Robert Burton's rhetoric : an anatomy of early modern knowledge - Wells, Susan, 1947- (RSA series in transdisciplinary rhetoric., 2019)
Published in five editions between 1621 and 1651, The Anatomy of Melancholy marks a unique moment in the development of disciplines, when fields of knowledge were distinct but not yet restrictive. In Robert Burton's Rhetoric, Susan Wells analyzes the Anatomy, demonstrating how its early modern practices of knowledge and persuasion can offer a model for transdisciplinary scholarship today. In the first decades of the seventeenth century, Robert Burton attempted to gather all the existing knowledge about melancholy, drawing from professional discourses including theology, medicine, and philology as well as the emerging sciences. Examining this text through a rhetorical lens, Wells provides an account of these disciplinary exchanges in all their subtle variety and abundant wit, showing that questions of how knowledge is organized and how it is made persuasive are central to rhetorical theory. Ultimately, Wells argues that in addition to a book about melancholy, Burton's Anatomy is a meditation on knowledge. A fresh interpretation of The Anatomy of Melancholy, this volume will be welcomed by scholars of early modern English and the rhetorics of health and medicine, as well as those interested in transdisciplinary work and rhetorical theory